Nomogram for predicting traumatic subdural effusion after mild traumatic brain injury - Wei, Lichao; Chang, Bowen; Geng, Zhi; Chen, Ming; Cao, Yongsheng; Yao, Liang; Ma, Chao (Frontiers in Neurology, 2022)
Objective Traumatic subdural effusion (TSE) is a common complication of traumatic brain injury (TBI). This study aimed to determine the risk factors associated with subdural effusion and to propose a nomogram to predict the risk of TSE in patients with mild TBI. Methods We retrospectively analyzed 120 patients with mild TBI between January 2015 and December 2020 at the Third People's Hospital of Hefei. The risk factors of TSE were selected using univariate and multivariable logistic regression analysis. A nomogram was developed to predict the incidence of TSE. Receiver operating characteristics and calibration plots were used to evaluate the discrimination and fitting performance. Results Of the 120 patients, 32 developed subdural effusion after mild TBI. Univariate analysis showed that gender, age, history of hypertension, traumatic subarachnoid hemorrhage, subdural hematoma, basilar skull fracture, and cerebral contusion were varied significantly between groups (p < 0.05). Logistic multivariate regression analysis showed that the gender, age, history of hypertension, and basilar skull fracture were independent risk factors for TSE. Based on these results, a nomogram model was developed. The C-index of the nomogram was 0.78 (95% CI: 0.70–0.87). The nomogram had an area under the receiver operating characteristic curve of 0.78 (95% CI: 0.70–0.87). The calibration plot demonstrated the goodness of fit between the nomogram predictions and actual observations. Conclusion Gender, age, history of hypertension, and basilar skull fracture can be used in a nomogram to predict subdural effusion after mild TBI.